2004
DOI: 10.1021/nl0492988
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Interdiffusion of Template-Synthesized Au/Sn/Au Junction Nanowires

Abstract: Microstructure and interdiffusion of striped Au/ Sn/Au nanowires grown by sequential electrodeposition of Au and Sn in porous polycarbonate membranes were investigated by X-ray diffraction, HRTEM, STEM, EDS, and electrical transport measurements. The Au/Sn junctions were found to contain two intermetallic phases: AuSn, and AuSn 4 . Mechanisms for the formation of these intermetallic phases and the effect of these phases on the superconductivity of striped nanowires were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 29 publications
4
46
0
3
Order By: Relevance
“…44 This yields H 0 = 4.86 μm per coulomb, corresponding to an efficiency of approximately 14%. In comparison, the typical plating efficiency in metal-backed AAO templates without a PEI adhesion layer is 70%.…”
Section: Resultsmentioning
confidence: 99%
“…44 This yields H 0 = 4.86 μm per coulomb, corresponding to an efficiency of approximately 14%. In comparison, the typical plating efficiency in metal-backed AAO templates without a PEI adhesion layer is 70%.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this section is to present microdevices specially designed for the correlated characterization of single hybrid metal-CP NWs but it could obviously be applied to other class of hybrid NWs such as hybrid inorganic NWs [Wang (2004)]. We address here the NWs assemblies with membrane-based micro-electromechanical systems.…”
Section: Correlated Characterizationmentioning
confidence: 99%
“…Metal Deposition potentiostatic conditions. In the case of track-etched PC, it was recently shown that the addition of 1-2% gelatin to the plating solution improves the wettability of the nanoporous membrane, thus improving the reproducibility of the electrodeposition step (45,(48)(49)(50).…”
Section: Electrochemical Depositionmentioning
confidence: 99%